2023
DOI: 10.1111/clr.14106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental implant therapy on the preservation of orofacial tissues: A systematic review and meta‐analysis

André B. De Souza,
Panos Papaspyridakos,
Hans‐Peter Weber
et al.

Abstract: ObjectiveFundamentally, this review addresses the following question: In partially or fully edentulous patients, do implant‐supported dental prostheses preserve orofacial tissues when compared to conventional prostheses or no therapy?Materials and MethodsThis study was conducted according to the 2020 PRISMA guidelines for systematic reviews. Electronic searches were conducted at PubMed and Embase databases followed by manual search. Clinical studies comparing the effect of implant‐supported prostheses with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Although this review also identified studies for evaluating the effect of implant‐supported rehabilitation on the masseter muscle thickness (Amaral et al, 2019; Maniewicz et al, 2019; Müller et al, 2012; 2013), this parameter was excluded from this review since it is not oral function and will be presented in one of the other ITI consensus papers (De Souza et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Although this review also identified studies for evaluating the effect of implant‐supported rehabilitation on the masseter muscle thickness (Amaral et al, 2019; Maniewicz et al, 2019; Müller et al, 2012; 2013), this parameter was excluded from this review since it is not oral function and will be presented in one of the other ITI consensus papers (De Souza et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of dental implant therapy on the preservation of orofacial tissues: a systematic review and meta‐analysis (De Souza et al, 2023). [Correction made October 2023, after original online publication: reference year ‘2023’ added here and in reference list].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…3. Effect of dental implant therapy on the preservation of orofacial tissues: a systematic review and meta-analysis (De Souza et al, 2023).…”
Section: Oral Function In Completely Edentulous Patients Rehabilitatedmentioning
confidence: 99%
See 1 more Smart Citation